Pembinaan Edukasi Finansial Pada Anak Melalui Menabung Sejak Dini Untuk Membangun Kemandirian Keuangan - Hikmah, Hikmah; Setiawati, Kiki; Saputri, Chika (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2019)
Financial management needs to be taught from an early age, with the hope that children can manage finances wisely and form good character. Learning to live frugal and not wasteful and not fall into a consumptive lifestyle. Parents need to provide examples and examples of this through appropriate parenting. The rise of children's snacks that circulate both at home and school environment, requires parents to be active and creative in setting an example, especially in terms of financial management of children. Teach children a frugal life, spend something to taste without being excessive and practicing for a simple life is the key to teaching children about financial management. The dedication was carried out at the Perumahan Air Mas Plaza Kelurahan Sei Langkai Kecamatan Sagulung. This coaching was conducted twice, where housewives were given an understanding of the importance of financial education for financial independence and then were given practice by learning by doing methods.